When Father Steps Forward and Mother Steps Back: The Moderating Role of Simultaneity in Parents' Coparenting Behaviors in the Development of Anxiety in 4‐ to 30‐Month‐Olds. (19th July 2017) - Metz, Marijke; Colonnesi, Cristina; Majdandžić, Mirjana; Bögels, Susan M.
Abstract : Infant negative affectivity predicts child anxiety. Coparenting might influence the development of anxiety by weakening this association in the case of supportive coparenting, or by strengthening this association in the case of undermining coparenting. Parents can display coparenting behaviors simultaneously (both parents being supportive or undermining), or divergently (only one parent being supportive or undermining). In our longitudinal study, we investigated whether coparenting moderated the relation between infant negative affectivity at 4 months and child anxiety symptoms 2 years later. Hundred‐sixteen couples dressed up their firstborn infants in a clothes‐changing task. We coded cooperative, mutual, neutral, and competitive coparenting behaviors. Both parents rated infant negative affectivity and child anxiety symptoms. Infant negative affectivity significantly predicted child anxiety. This association was moderated by parents' divergent cooperative coparenting: It was stronger when mothers were cooperative while fathers were neutral, and weaker when fathers were cooperative while mothers were neutral. When fathers step forward (i.e., being cooperative) and mothers step back (i.e., leaving space), they may protect their at‐risk child from developing anxiety.